Microbiological Evaluation of Fresh Retail Rabbit Meat Cuts from Zagazig City, Egypt - Mahmoud, Abdallah Fikry A.; Hafez , Abd El-Salam E.; Abdullatif, Afnan Fouad; Ras, Refaat Atef M.; Abdallah, Hossam M.; Shata , Rania Helmy M.; El Bayomi, Rasha M. (Journal of Advanced Veterinary Research, 2022)
The present study was conducted to evaluate the microbiological status of rabbit carcasses marketed in Zagazig City, Sharkia province, Egypt. Eighty random samples of fresh rabbit meat cuts representing shoulder, loin, ribs, and thigh regions (20 of each) were obtained from different rabbit markets in Zagazig City during 2022. Aerobic plate count (APC), Enterobacteriaceae, total mould and yeast counts were determined in the collected samples, as well as the isolation and identification of E. coli and Salmonella spp. The results showed that the mean values of APC and Enterobacteriaceae were 1.1x106 and 4.7x104 CFU/g for shoulders, 9.6x105 and 5.7x104 CFU/g for ribs, 1.0x106 and 5.1x104 CFU/g for loins, 1.2x106 and 6.0x104 CFU/g for thigh samples, respectively. Moreover, the total mould and yeast count ranged from 2.6x104 to 1.9x105 with mean values of 9.7x104 ± 1.1x104, 8.2x104 ± 9.9x103, 9.5x104 ± 1.4x104 and 9.8x104 ± 8.5x103 CFU/g in the of examined rabbit meat samples from shoulder, ribs, loin, and thigh regions, respectively. In terms of food poisoning bacteria, 6 (30 %), 7 (35 %), 6 (30 %) and 4 (20 %) out of 20 rabbit cuts tested positive for Salmonellae in the shoulder, ribs loin, and thigh regions, respectively. However, E. coli was found in 18 (90%), 16 (80%), 15 (75%) and 19 (95%) of the examined rabbit meat samples, respectively. The obtained results suggested that fresh rabbit meat cuts may carry numerus microorganisms from different sources, emphasizing the importance of stringent sanitary precautions during the slaughtering, handling and cooking procedures.